Addressing the Overheating Crisis and Its Socio-Economic Implications: A Case Study in London’s High-Risk Areas - Maliha, Azra (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)